Perbandingan Motivasi Kerja Ruang Rawat Inap dan Ruang Operasi dalam Pelaksanaan Pendokumentasian di RS MTSJ - Risma Tio Siahaan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Based on the results of a preliminary study conducted by researchers in January in the inpatient room and operating room at MTSJ Hospital, it was found that there was still a lot of incomplete documentation. Of the 10 murder documentation, 7 of them are still incomplete, incomplete documentation, starting from not including all the acts committed by the murder, inaccuracy in the signature of informed consent between the witness and the patient, unavailability in the form of a fall risk for pediatric and geriatric patients. Documentation at MTSJ Hospital still receives little attention, so care documents are still found whose contents are incomplete. Some problems with documenting nursing care include: lack of motivation in documenting nursing care, writing documentation is considered time-consuming and focuses on patient care. Incomplete documentation will cause losses to clients because important information related to their care and health conditions is neglected. Inefficient and ineffective documentation due to inadequate quality and accuracy causes communication errors between nurses and other professions. Based on the description above and the results of preliminary research, researchers are interested in researching the comparison of work motivation in inpatient rooms and operating rooms with the implementation of documentation at MTSJ Hospital.